PENDEKATAN HOLISTIK DAN KONTEKSTUAL DALAM MENGATASI KRISIS KARAKTER DI INDONESIA - Astuti, Siti Irene (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: A Holistic and Contextual Approach to Overcome Character Crisis inIndonesia. Indonesia has been confronting character crisis structural in nature as itoccurs in all orders of societys life. Life practice has lost its important valuesneeded to build people with character. Such values as honesty, self-confidence,appreciation to diversity, and enthusiasms for learning and working have beendecreasing. Actually, such values play an important role in solving problems thatIndonesia is now facing, such as corruption, continuous-horizontal conflicts,inferior feelings, and low enthusiasms for learning and working. In relation to this,education can be a means to build people with character. It can be implementedwith a holistic and contextual approach. Such an approach deals with not only thecognitive factor but also all potentials belonging to people. Principles of charactereducation should be socialized and implemented in all levels of society.Keywords: character education, holistic and contextual approach